TREATMENT OF COGNITIVE DISORDERS IN HYPERTENSIVE PATIENTS EXPOSED TO RADIATION - I. V. Podsonnaja; G. G. Efremushkin; V. A. Golovin (Столичная издательская компания, 2016)
Aim. To assess cognitive functions in liquidators of Chernobyl accident (LCA) consequences suffering from arterial hypertension (HT) and to study efficacy of their treatment with cortexin (complex of polypeptide fractions).Material and methods. 60 men (aged of 39-60 y.o.), LCA with HT and cognitive disorders were included in the study. Cortexin was used (10 mg intramusculary during 10 days) for one or two courses. Efficacy of treatment was estimated by neuropsychological tests (Shulte test , A.R. Lurija test, serial account, test "feeling, activity, mood", headache intensity on VAS scale) before and in 10 days of treatment as well as 6 and 12 months after treatment.Results. Cortexin therapy (2 courses) increased of mental processes speed and retention of information volume, reduced personal and behavioral disorders.Conclusion. Treatment with cortexin (2 courses) improves cognitive functions in LCA with HT.